Kinerja Dinas Perhubungan Pada Unit Pelaksana Teknis Daerah (UPTD) Danau Panggang Dalam Penarikan Retribusi Pelayanan Kepelabuhan Dermaga Danau Panggang Kabupaten Hulu Sungai Utara - Muhamad Arsyad; Risnawati (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: This research is motivated by issues such as the inconsistency of tariffs with regulations, the collection of service fees without tickets, and suboptimal service delivery. A qualitative approach was used, with data collected through interviews, observation, and documentation. Data sources were selected through purposive sampling, involving 13 participants. The data were analyzed using techniques of data reduction, data presentation, and drawing conclusions. Credibility testing was conducted through prolonged observation, increased diligence, triangulation, reference materials, and member checking. The results indicate that performance was less than satisfactory. Indicators showing poor performance included service compliance, program development, accuracy, and thoroughness. Fairly good indicators included work results, efficiency, public satisfaction, accountability, and compliance with organizational policies. Meanwhile, organizational capability and the presence of Standard Operating Procedures (SOPs) were assessed as good. Supporting factors included good attitudes and a sense of responsibility, The inhibiting factors are the absence of technology use in the retribution collection process, such as the use of QRIS for payments, and the implementation that does not comply with the SOP. It is recommended to improve supervision, evaluation, discipline, and employee professionalism in carrying out their duties